Pelaksanaan Perjanjian Sewa Menyewa Kios Milik Koperasi Pondok Pesantren Al-Mutmainnah : (Sudi Pasar Syari’ah Desa Dasan Baru Lombok Barat) - M. Syaefurrahman Jazaqi; Salim HS (Private Law, 2022)
This study aims to find out and explain about the implementation of the lease agreement of the stalls owned by the cooperation of AL-Mutmainnah Islamic Boarding School and to find out the settlement of dispute in the event of default of such agreement. This study is an empirical legal research. The results of the study show that the implementation of the lease agreement of the stalls is carried out in the form of a standard agreement which is embodied into a agreement letter. The form of dispute resolution of the lease agreement of the stands owned by the cooperation of AL-Mutmainnah Islamic Boarding School Cooperative is by way of an out-court resolution (non-litigation), by way of negotiation and mediation through deliberation to reach consensus or through amicable settlement which directly involves both parties.